PSIV-10 Effects of stair-step vs. constant supplementation amount on growth, reproduction, and intravaginal temperature in Bos indicus-influenced beef heifers. (30th November 2020) - Palmer, Elizabeth A; Oliveira, Rhaiza A; Binelli, Mario; Martins, Thiago; Vendramini, João; Moriel, Philipe
Abstract: This study investigated growth and reproductive performance of Bos indicus-influenced beef heifers provided a concentrate supplement at either a constant or stair-step supplementation. Sixty-four Brangus heifers were stratified by initial BW and age (255 ± 20 kg; 270 ± 22 d) and assigned to 1 of 16 bahiagrass pastures (4 heifers/pasture). Treatments were randomly assigned to pastures (8 pastures/treatment) and consisted of concentrate DM supplementation at: (1) 1.50% of BW from d 0 to 100 (CON) and (2) 1.05% of BW from d 0 to 49 and 1.95% of BW from d 50 to 100 (STP). Supplementation started on d 0 and continued until start of estrous synchronization on d 100. Intravaginal temperatures (16 heifers/treatment) were collected every 30 minutes from d 25 to 31 (September) and d 85 to 91 (November). All heifers were provided supplement at 1.50% of BW from d 101 to 211. Heifers were bred by AI from d 113 to 115 and Brangus bulls were placed with heifers from d 121 to 211. Data were analyzed using the MIXED procedure of SAS with treatment, time, and interaction as fixed effects. From d 0 to 49, ADG did not differ (P = 0.87); however, STP heifers had greater (P = 0.01; 0.73 vs. 0.56 kg/d) ADG from d 50 to 100 compared to CON heifers. Percentage of pubertal heifers, percentage of heifers in estrus, or reproductive tract scores did not differ between treatments (P ≥ 0.40). Intravaginal temperatures were greater (P < 0.0001) for CON vs. STP heifers from d 25 to 31 but did not differ (P = 0.74) from d 85 to 91. Using a stair-step vs. constant supplementation amount (1.05 to 1.95% vs. 1.50% of BW) before the breeding season reduced intravaginal temperatures and increased overall ADG in Bos indicus-influenced beef heifers.